2004
DOI: 10.1021/ie0307380
|View full text |Cite
|
Sign up to set email alerts
|

Heat Transfer to a Single Sphere Immersed in Beds of Particles Supplied by Gas at Rates above and below Minimum Fluidization

Abstract: The coefficient of heat transfer to a mobile sphere in a fluidized bed of relatively large particles has been measured. Measurements were also made for U < U mf , where the solids are stationary. One feature of these experiments is that the heat-transfer sphere was of a size comparable to that of the bed particles. Two methods of measuring heat-transfer coefficients in the bed were employed: (i) The rate of cooling of a sphere, initially hot, was measured by means of a tiny inserted thermocouple with fine lead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 13 publications
(54 reference statements)
4
26
0
Order By: Relevance
“…That Eq. (7) holds for U/U mf 1, as well as for U > U mf , but then using Re = U mf d s / , is confirmed by subsequent work by Scott et al (2004), who found a very similar correlation for spheres of the much lighter material graphite as the heat transfer particle. Given all the above, it might be expected that for the conditions of this study, there is the mass transfer analogue of Eq.…”
Section: Discussionsupporting
confidence: 52%
“…That Eq. (7) holds for U/U mf 1, as well as for U > U mf , but then using Re = U mf d s / , is confirmed by subsequent work by Scott et al (2004), who found a very similar correlation for spheres of the much lighter material graphite as the heat transfer particle. Given all the above, it might be expected that for the conditions of this study, there is the mass transfer analogue of Eq.…”
Section: Discussionsupporting
confidence: 52%
“…The cooling of copper spheres at different initial locations in a gas fluidzied bed was examined by the model (Zhou et al, 2009). In physical experiments, the temperature of hot spheres is measured using thermocouples connected to the spheres (Collier et al, 2004;Scott et al, 2004). But the cooling process of such hot spheres can be easily traced and recorded in the DPS-CFD simulations, as shown in Fig.…”
Section: Model Applicationmentioning
confidence: 99%
“…In physical experiments, Collier et al (2004) and Scott et al (2004) used different materials to examine the HTCs of hot spheres, and found that there is a general tendencyfor the HTC of hot sphere increasing first with gas superficial velocity in the fixed bed (U<U mf ), and then remaining constant, independent on the gas superficial velocities for fluidized beds (U>U mf ). The DPS-CFD simulation results also exhibit such a feature (Fig.…”
Section: Model Applicationmentioning
confidence: 99%
See 1 more Smart Citation
“…20,21 But in uidized beds, although researchers have paid much attention to this problem, their results are insufficient to reach a general conclusion. Behjat 22 and Yiannoulakis et al 23 found that the higher supercial velocity had a positive effect on the heat transfer coefficient, while Scott, 24 Zhou 25 and Li et al 13 found that increasing the gas velocity did not lead to an increase of the heat transfer coefficient. And for the effect of bed diameter, Matsen 26 found that larger units gave higher mixing rates, but there is no practicable conclusion for industrial uidized beds, since most of the experiments are in laboratory scale.…”
Section: Introductionmentioning
confidence: 99%